ENHANCING HEALTH AND PROMOTING A HEALTHY LIFESTYLE IN SAMARKAND: A COMPREHENSIVE APPROACH (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This scientific article explores strategies for improving health and fostering a healthy lifestyle in Samarkand, a historic city with a rich cultural heritage. The study delves into the current health status of the population and proposes interventions to promote well-being and prevent diseases. By integrating cultural sensitivity and community engagement, this research aims to contribute to the development of effective health promotion programs tailored to the unique needs of Samarkand's residents.